Metamorphosis at 'the margin' : Bruce Mason, James K. Baxter, Mervyn Thompson, Renée and Robert Lord, five playwrights who have helped to change the face of New Zealand drama : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in English at Massey University, Palmerston North, New Zealand - Williams, Susan Lillian (Massey University, 2006)
Drama has been the slowest of the arts to develop an authentic New Zealand 'voice.' This thesis focuses on the work of five playwrights: Bruce Mason, James K. Baxter, Mervyn Thompson, Renée and Robert Lord, all of whom have set out to identify such a 'voice' and in so doing have brought about a metamorphosis in the nature of New Zealand drama. New Zealand has traditionally been regarded as being on 'the margin' in relation to the dominant culture of the colonizer (the Eurocentre). Before Bruce Mason began to challenge this 'centre' of power in the early 1950s, New Zealand playwrights were so intimidated by the Eurocentre that they usually set their plays in Europe, particularly in England, in order to make them acceptable to their audiences. Mason proposed that 'the margin' of New Zealand, rather than being seen as inferior, should be redefined as a fertile place capable of nurturing a new individual dramatic form quite distinct from colonial norms. All of my chosen playwrights have insisted upon the intrinsic value of a two-tiered concept of 'the margin.' By setting their plays (wherever possible) in the country of their birth, highlighting New Zealand social issues and in the process persuading theatre-going audiences that plays about this country are worth watching, they have given new life to 'the margin' (the culture of New Zealand as a whole). At the same time all of these five playwrights have recognized that minority groups - 'voices' from 'the outer margin' in relation to the Pakeha 'inner margin' of power - have been largely unrepresented or misrepresented in New Zealand plays. They have advocated the vital importance of women's 'voices,' Māori 'voices' and gay 'voices,' for example, in their exploration of a more sophisticated and inclusive understanding of what constitutes our national identity. Moreover, in a period of less than forty years, they have helped to facilitate the transition of New Zealand theatre from amateur to professional status and have been instrumental in providing the practical framework whereby future New Zealand playwrights may find an outlet for their work.
Keywords: New Zealand theatre; New Zealand playwrights; Minority groups in drama; Fields of Research::410000 The Arts::410100 Performing Arts Studies::410102 Drama, theatre and performance studies